The association of red blood cell n‐3 and n‐6 fatty acids with bone mineral density and hip fracture risk in the women's health initiative. (15th February 2013) - Orchard, Tonya S; Ing, Steven W; Lu, Bo; Belury, Martha A; Johnson, Karen; Wactawski‐Wende, Jean; Jackson, Rebecca D
Abstract: Omega‐3 (n‐3) and omega‐6 (n‐6) polyunsaturated fatty acids (PUFA) in red blood cells (RBCs) are an objective indicator of PUFA status and may be related to hip fracture risk. The primary objective of this study was to examine RBC PUFAs as predictors of hip fracture risk in postmenopausal women. A nested case‐control study ( n  = 400 pairs) was completed within the Women's Health Initiative (WHI) using 201 incident hip fracture cases from the Bone Mineral Density (BMD) cohort, along with 199 additional incident hip fracture cases randomly selected from the WHI Observational Study. Cases were 1:1 matched on age, race, and hormone use with non–hip fracture controls. Stored baseline RBCs were analyzed for fatty acids using gas chromatography. After removing degraded samples, 324 matched pairs were included in statistical analyses. Stratified Cox proportional hazard models were constructed according to case‐control pair status; risk of fracture was estimated for tertiles of RBC PUFA. In adjusted hazard models, lower hip fracture risk was associated with higher RBC α‐linolenic acid (tertile 3 [T3] hazard ratio [HR]: 0.44; 95% confidence interval [CI], 0.23–0.85; p for linear trend 0.0154), eicosapentaenoic acid (T3 HR: 0.46; 95% CI, 0.24–0.87; p for linear trend 0.0181), and total n‐3 PUFAs (T3 HR: 0.55; 95% CI, 0.30–1.01; p for linear trend 0.0492). Conversely, hip fracture nearly doubled with the highest RBC n‐6/n‐3 ratio (T3 HR: 1.96; 95% CI, 1.03–3.70; p for linear trend 0.0399). RBC PUFAs were not associated with BMD. RBC PUFAs were indicative of dietary intake of marine n‐3 PUFAs (Spearman's rho = 0.45, p  < 0.0001), total n‐6 PUFAs (rho = 0.17, p  < 0.0001) and linoleic acid (rho = 0.09, p  < 0.05). These results suggest that higher RBC α‐linolenic acid, as well as eicosapentaenoic acid and total n‐3 PUFAs, may predict lower hip fracture risk. Contrastingly, a higher RBC n‐6/n‐3 ratio may predict higher hip fracture risk in postmenopausal women. © 2013 American Society for Bone and Mineral Research.